Machine Learning Decision Tree Models for Differentiation of Posterior Fossa Tumors Using Diffusion Histogram Analysis and Structural MRI Findings - Payabvash, Seyedmehdi; Aboian, Mariam; Tihan, Tarik; Cha, Soonmee (Frontiers in Oncology, 2020)
We applied machine learning algorithms for differentiation of posterior fossa tumors using apparent diffusion coefficient (ADC) histogram analysis and structural MRI findings. A total of 256 patients with intra-axial posterior fossa tumors were identified, of whom 248 were included in machine learning analysis, with at least 6 representative subjects per each tumor pathology. The ADC histograms of solid components of tumors, structural MRI findings, and patients’ age were applied to construct decision models using Classification and Regression Tree analysis. We also compared different machine learning classification algorithms (i.e. naïve Bayes, random forest, neural networks, support vector machine with linear and polynomial kernel) for dichotomized differentiation of the 5 most common tumors in our cohort: metastasis (n=65), hemangioblastoma (n=44), pilocytic astrocytoma (n=43), ependymoma (n=27), and medulloblastoma (n=26). The decision tree model could differentiate seven tumor histopathologies with terminal nodes yielding up to 90% accurate classification rates. In receiver operating characteristics (ROC) analysis, the decision tree model achieved greater area under the curve (AUC) for differentiation of pilocytic astrocytoma (p=0.020); and atypical teratoid/rhabdoid tumor ATRT (p=0.001) from other types of neoplasms compared to the official clinical report. However, neuroradiologists’ interpretations had greater accuracy in differentiating metastases (p=0.001). Notably, while the number of patients with ATRT (n=6) was too small to draw a firm conclusion, patients’ age of 3 years and low ADC values (5th percentile <658 ×10-6mm2/s) in the solid component could identify 5 out of 6 ATRTs in our cohort with 71% positive predictive value. Among different machine learning algorithms, random forest models yielded the highest accuracy in dichotomized classification of the 5 most common tumor types; and in multiclass differentiation of all tumor types random forest yielded an averaged AUC of 0.961 in training datasets, and 0.873 in validation samples. Our proof of concept study demonstrates the potential application of machine learning algorithms and decision trees for accurate differentiation of brain tumors based on pretreatment MRI. Using easy to apply and understandable imaging metrics, the proposed decision tree model can help radiologists with differentiation of posterior fossa tumors, especially in tumors with similar qualitative imaging features.